2008
DOI: 10.1070/sm2008v199n03abeh003922
|View full text |Cite
|
Sign up to set email alerts
|

Affine toric SL(2)-embeddings

Abstract: In 1973 V.L.Popov classified affine SL(2)-embeddings. He proved that a locally transitive SL(2)-action on a normal affine three-dimensional variety X is uniquely determined by a pair ( p q , r), where 0 < p q ≤ 1 is an uncancelled fraction and r is a positive integer. Here r is the order of the stabilizer of a generic point. In this paper we show that the variety X is toric, i.e. admits a locally transitive action of an algebraic torus, if and only if r is divisible by q − p. To do this we prove the following … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…This construction has already been used in affine algebraic geometry. For example, the calculation of the Cox ring allowed to characterize affine SL(2)-embeddings that admit the structure of a toric variety [11]. In [4], it is shown that Cox realization leads to a remarkable unified description of all affine SL(2)-embeddings, which was not known before.…”
Section: Introductionmentioning
confidence: 99%
“…This construction has already been used in affine algebraic geometry. For example, the calculation of the Cox ring allowed to characterize affine SL(2)-embeddings that admit the structure of a toric variety [11]. In [4], it is shown that Cox realization leads to a remarkable unified description of all affine SL(2)-embeddings, which was not known before.…”
Section: Introductionmentioning
confidence: 99%
“…(q, p) = 1. Theorem 3.2 ( [Gaȋ08], see also [BH08,Corollary 2.7]). An affine normal quasihomogeneous SL(2)-variety E l,m is toric if and only if q − p divides m.…”
Section: Q Sl(2)-mentioning
confidence: 99%
“…, where E − l,m and E + l,m are different GIT quotients of H q−p corresponding to some non-trivial characters, and that the varieties E l,m , E − l,m , and E + l,m are dominated by the weighted blow-up E ′ l,m = Bl ω O (E l,m ) of E l,m with a weight ω defined by the abovementioned C * -action on E l,m . The weight ω is trivial if and only if the SL(2)-variety E l,m is toric, namely if m = a(q − p) holds for some a > 0 (see [Gaȋ08,BH08]).…”
mentioning
confidence: 99%
“…(q, p) = 1. Theorem 2.2 ( [Gaȋ08], see also [BH08,Corollary 2.7]). An affine normal quasihomogeneous SL(2)-variety E l,m is toric if and only if q − p divides m.…”
Section: Theorem 21 ([Pop73]mentioning
confidence: 99%
“…The smoothness of the invariant Hilbert scheme H is independent of the pair of numbers (l, m), but the behavior of the resolution γ does depend on it: it depends on whether E l,m is toric or not. Here we remark that a necessary and sufficient condition for E l,m being a toric variety is given in [Gaȋ08] (see also [BH08, Corollary 2.7]) in terms of the numbers l = p/q and m: an affine variety E l,m is toric if and only if q − p divides m. In both toric and non-toric case, we see that the restriction of γ to the main component H main = γ −1 (U) of the invariant Hilbert scheme H factors equivariantly through the weighted blow-up E ′ l,m :…”
mentioning
confidence: 99%